Penentuan Mutu Cabai Rawit Segar (Capsicum frutescens L.) Berdasarkan Perubahan Warna Selama Penyimpanan MAP - Erni Romansyah; Nursigit Bintoro; Joko Nugroho Wahyu Karyadi; Arifin Dwi Saputro (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2024)
The decline in the quality of cayenne pepper can be seen directly from the color change. The objective of this study was to classify classifies the quality of fresh cayenne pepper based on color changes during storage. In addition, the kinetics model of color change was also established. Samples were stored in 50 µm thick polyethylene (PE) packaging at 15°C. Then, for 14 days, the CIE L* a* b* color was taken. Control storage without packaging at room temperature was carried out as a control. Using PCA analysis, the quality of fresh cayenne pepper could be classified. This study found a more than 99% difference between the two groups of fresh cayenne pepper. PC1 explained 85.6%, PC2 13.5%, total PC 99.1% for T15°C; and PC1 81.6%, PC2 15.7%, total PC 97.3% for the control sample. The rate of color change per day for °Hue followed second-order kinetics, while Chroma and ∆E followed zero-order kinetics of 0.0008, 0.6524, and 1.0822 C-unit-1.hari-1, respectively, for T15°C samples, and 0.0027; 0.8099; and 1.8231 C-unit.hari-1 respectively for control samples.